Makibaa: The Living out Experience Among the iMiligan of Upper Bauko, Mountain Province - Samonte, L L (KnE Social Sciences, 2018)
This study was conducted to find out why iMiligan youth leave their biological families and live with non-relatives in other provinces in the lowlands (Makibaa). It also studied the problems they encountered and how they managed such problems. Using a descriptive-qualitative-exploratory method, responses had been identified through key informant interviews and focus group discussions. Findings revealed that the participants moved to various destinations in the lowlands due to push and pull factors. The push factors were economic, geographical, social, political and education. The pull factors were availability and proximity of schools, educational opportunities, values and skills’ development and higher demand from foster parents. Participants described their stay in the lowlands as memorable, rewarding, and gratifying although some encountered negative experiences. Varied strategies were employed by the foster children in response to the negative encounters. The choice of destinations and prospective foster families followed some dynamics such as referrals from former or current baa; by invitation from prospective foster parents or referrals of foster parents; and through request by biological parents for foster families. Keywords: Baa, iMiligan, Igorots, Living out, Makibaa